Numerical Analysis - MTH603 Handouts Lecture 19
Numerical Analysis - MTH603 Handouts Lecture 19
Backward Differences
For a given table of values ( xk , yk ), k = 0,1, 2,..., n of a function y = f (x) with equally
spaced abscissas, the first backward differences are usually expressed in terms of the
backward difference operator ∇ as
∇yi = yi − yi −1i = n, (n − 1),… ,1
To be explicit, we write
∇y1 = y1 − y0
∇y2 = y2 − y1
OR
∇yn = yn − yn −1
The differences of these differences are called second differences and they are denoted by
∇ 2 y2 , ∇ 2 y3 ,… , ∇ 2 yn .
∇ 2 y1 = ∇y2 − ∇y1
∇ 2 y2 = ∇y3 − ∇y2
That is
∇ 2 yn = ∇yn − ∇yn −1
Thus, in general, the second backward differences are
∇ 2 yi = ∇yi − ∇yi −1 , i = n, (n − 1),..., 2
While the k-th backward differences are given as
∇ k yi = ∇ k −1 yi − ∇ k −1 yi −1 , i = n, (n − 1),..., k
These backward differences can be systematically arranged for a table of values
( xk , yk ), k = 0,1,..., 6 shown below.
Backward Difference Table
From this table, it can be observed that the subscript remains constant along every
backward diagonal.
Example
Show that any value of y can be expressed in terms of y and its backward differences.
n
Solution:
From
∇yi = yi − yi −1i = n, (n − 1),… ,1
We get
yn −1 = yn − ∇yn yn − 2 = yn −1 − ∇yn −1
yn −1 = (1 − ∇) yn
yn − 2 = (1 − ∇) 2 yn
yn −3 = (1 − ∇)3 yn
.......
yn − r = (1 − ∇) r yn
δ y1 2 = y1 − y0 , δ y3 2 = y2 − y1 ,
In General,
δ yi = yi + (1 2) − yi −(1 2)
δ n yi = δ n −1 yi + (1 2) − δ n −1 yi −(1 2)
These central differences can be systematically arranged as indicated in the Table
Thus, we observe that all the odd differences have a fractional suffix and all the even
differences with the same subscript lie horizontally.
The following alternative notation may also be adopted to introduce finite difference
operators. Let y = f (x) be a functional relation between x and y, which is also denoted by
y .
x
Suppose, we are given consecutive values of x differing by h say x, x + h, x +2h, x +3h,
etc. The corresponding values of y are y x , y x + h , yx + 2 h , yx +3h ,
As before, we can form the differences of these values.
Thus
∆y x = y x + h − y x = f ( x + h) − f ( x)
∆ 2 y x = ∆yx + h − ∆yx
Similarly,
∇y x = y x − y x − h = f ( x ) − f ( x − h )
h h
δ yx = yx + ( h / 2) − yx −( h / 2) = f x + − f x −
2 2
To be explicit, we write
∆y0 = y1 − y0
∆y1 = y2 − y1
∆yn −1 = yn − yn −1
∇yn = yn − yn −1
δ y1 2 = y1 − y0 , δ y3 2 = y2 − y1 ,
In General,
δ yi = yi + (1 2) − yi −(1 2)
Higher order differences are defined as follows:
δ 2 yi = δ yi + (1 2) − δ yi −(1 2)
δ n yi = δ n −1 yi + (1 2) − δ n −1 yi −(1 2)